2011
DOI: 10.1016/j.neuroimage.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of ocular-muscle EMG contamination in human intracranial recordings

Abstract: It is widely assumed that intracranial recordings from the brain are only minimally affected by contamination due to ocular-muscle electromyogram (oEMG). Here we show that this is not always the case. In intracranial recordings from five surgical epilepsy patients we observed that eye movements caused a transient biphasic potential at the onset of a saccade, resembling the saccadic spike potential commonly seen in scalp EEG, accompanied by an increase in broadband power between 20 and 200 Hz. Using concurrentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 53 publications
6
107
0
Order By: Relevance
“…4) per second, and thus EM-driven activity would have taken the form of random sparse bursts in single trials, but these were not consistently observed. Second, although eye movements could not be tracked with fidelity in the clinical ICU setting, saccadic spike potentials elicited by the contraction of the ocular muscles at the onset of saccades (Yuval-Greenberg et al, 2008), can be detected intracranially in electrodes proximal to the eyes (Jerbi et al, 2009; Kovach et al, 2011). We were able to identify reliable saccadic events in one of our patients through the detection of intracranial saccadic spike potentials in two temporal pole electrodes, just posterior to the eye (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4) per second, and thus EM-driven activity would have taken the form of random sparse bursts in single trials, but these were not consistently observed. Second, although eye movements could not be tracked with fidelity in the clinical ICU setting, saccadic spike potentials elicited by the contraction of the ocular muscles at the onset of saccades (Yuval-Greenberg et al, 2008), can be detected intracranially in electrodes proximal to the eyes (Jerbi et al, 2009; Kovach et al, 2011). We were able to identify reliable saccadic events in one of our patients through the detection of intracranial saccadic spike potentials in two temporal pole electrodes, just posterior to the eye (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to functional MRI, HIE techniques offer comparable spatial resolution but with microsecond temporal resolution which is on the same order of magnitude as the speed of cognitive processing. Furthermore, HIE recordings are somewhat immune to muscle and eye movement artifact (Kovach et al, 2011). This allows for the study of phenomena involving motor actions which is difficult when using functional MRI, such as laughter.…”
Section: Human Intracranial Electrophysiologymentioning
confidence: 99%
“…While intracranial recordings may occasionally be contaminated by eye muscle activity (Ball et al 2009;Jerbi et al 2009a;Kovach et al 2011), these effects are predominantly restricted to recordings sites in the vicinity of the temporal pole and are efficiently reduced by using bipolar re-referencing strategies (Jerbi et al 2009a). Certainly, these recordings are performed in patients with brain pathologies, so individual results are best interpreted in the context of converging evidence from other techniques; nevertheless, each patient's pathology tends to be different; therefore, findings that remain consistent across patients can be regarded with reasonable confidence (Jerbi et al 2009b).…”
Section: Intracranial Eeg and Cortical Rhythmsmentioning
confidence: 99%